Dental cingulum: Literature review - Moreno, Sandra; Moreno, Freddy (Revista Estomatología, 2016)
In the anthropological context, dental cingulum is recognized as a enamel structure that surrounds of all teeth on the cervical third, and which has the function of protecting the periodontal tissues of the fragments of food during mastication, dissipate the vertical forces during occlusion and provide a platform for the morphogenetic development of some dental morphological features. However, in the dental context, these functions of dental cingulum are misunderstood, primarily the development of morphological structures such as the dental tubercle, the interruption groove, the Carabelli trait, the parastyle and the protostylid. That is why this literature review aims to contrast the anthropological and odontological concepts, to the lack of understanding of the dental cingulum by the vast majority of oral health professionals. Keywords: Dental Anthropology, dental morphology, dental cingulum, non-metric dental traits, dental morphogenesis.